Detanning of Deoiled Sal (Shorea robusta) Seed Meal by a 4-Stage Counter Current Extraction with Aoueous Ethanol - Sanjiva Rao, V.; Madhusudana Rao, K. (Indian Forester, 1985)
Detanning of Deoiled Sal Seed Meal (DSSM) is studied in a 4-stage counter current extraction system using aqueous ethanol (50% v/v.) as solvent. With a solvent to cake ratio of 5 : 1, tannin extractabilities of 57 to 70 per cent are achieved, while the tannin content of DSSM is reduced to 7.42 and 9.16 per cent from original cake having tannin content of 17-75 and 18.71 per cent respectively. Analysis of final liquor obtained in 4-stage extraction, indicate that the tannin and total soluble contents of 17 g/lit. and 34 g/lit, can be raised by employing a 6-stage system for tannin recovery from the liquor.